1988
DOI: 10.1093/infdis/157.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carriage of Antibiotic-Resistant Pneumococci by Children in Group Day Care

Abstract: We compared rates of antibiotic resistance in strains of Streptococcus pneumoniae recovered from nasopharyngeal secretions of a group of children studied longitudinally in a research day care center between 1978 and 1985 and recovered from usually sterile body fluids of patients at a tertiary care hospital between 1981 and 1985. The prevalence of trimethoprim-sulfamethoxazole (TMP-SMZ) resistance was 11.5% in isolates from the hospital, whereas 30.0% of episodes of nasopharyngeal carriage of S. pneumoniae stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1
3

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(51 citation statements)
references
References 26 publications
3
44
1
3
Order By: Relevance
“…[26][27][28] A number of studies have demonstrated a strong association between daycare attendance and increased carriage of S. pneumoniae, especially of resistant strains. 13,28,29 Study findings demonstrated that daycare attendance and patterns of antibiotic use may be important factors influencing the epidemiology of antibiotic-resistant bacteria.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…[26][27][28] A number of studies have demonstrated a strong association between daycare attendance and increased carriage of S. pneumoniae, especially of resistant strains. 13,28,29 Study findings demonstrated that daycare attendance and patterns of antibiotic use may be important factors influencing the epidemiology of antibiotic-resistant bacteria.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings supports earlier studies from similar centers over the last decade. [9][10][11][12][13][14][15][16][17][18][19][20][21] Recent research established daycare attendance as an important factor influencing the epidemiology of many infectious diseases. [26][27][28] A number of studies have demonstrated a strong association between daycare attendance and increased carriage of S. pneumoniae, especially of resistant strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a disease of continuing endemicity particularly in infancy and old age [6]. Day care centres are very likely to be places for spread of organisms in toddlers [7,8,9,10]. In military medical literature, there are accounts of pneumococcal outbreaks.…”
Section: Discussionmentioning
confidence: 99%